THEMES OF SOLITUDE AND DEATH: IN LITERARY TEXTS (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2018)
Solitude allows one to explore one’s own mind without outside interference. A person gets enough time for selfintrospection to understand the best course to apply to make life bearable apart from developing positive thoughts for those who are responsible for negativity in one’s life. A solitary worker is taken to be a productive and creative worker. But too much of anything can be bad. And time and again authors have dealt with this issue of solitary existence. Solitude becomes source of sickness when man being a social animal misses out on the need to have human connect. Much read work of Gabriel Garcia Marquez, One Hundred Years of Solitude, might strike a chord with those who believe in Stoicism that people go through periods of solitary existence through circumstances, generally not created by them.